A preliminary study of patient-specific differences in induced pluripotent stem cell-derived cardiomyocytes following hypoxia-induced injury. (10th June 2022) - Derish, I; Zwaig, J; Khan, K; Derish, D; To, J; Young, P; Cecere, R
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Courtois Cardiovascular Signature Program The increasing rate of cardiovascular disease (CVD) contributes to a worsening morbidity in the general population and a socioeconomic burden on the healthcare system. Newly approved therapies present unforeseen side effects and occasionally entail adverse cardiovascular responses in patients - this issue significantly stalls efficacious pharmacological development. Indeed, modern cardiovascular treatments do not account for the variability of individual patient reactions, due to a lack of a representative in vitro cardiac model. While the use of induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) has gained traction as a superior model for drug screening when compared to cardiac biopsies and immortalized cell lines, cardiovascular patient-specific differences remain poorly understood and understudied. We hypothesized that 1) cardiomyopathic patient-derived iPSC-CMs have differing baselines of beating rate, contractility, viability, metabolic activity and protein expression, when compared to healthy controls, and that 2) cell lines have patient-specific responses to hypoxia-induced injury. As such, the purpose of this preliminary study was two-fold: 1) to perform a characterization of patient iPSC-CM function, and 2) to study patient-specific cellular responses to hypoxia. First, we generated iPSC-CMs from the peripheral blood of donors (n=6 patients with cardiomyopathies, n=2 healthy donors). We then confirmed the expression of prominent cardiac markers connexin 43 (CXN43), sarcoendoplasmic reticulum Ca2+ ATPase (SERCA2a), GATA4 and cardiac Troponin T, as well as a lack of pluripotency markers Octamer-binding transcription factor 4 (OCT4), Nanog, Stage-specific embryonic antigen-4 (SSEA-4) and TRA-1-60 in the iPSC-CM lines, via immunocytochemistry. Preliminary assessment of iPSC-CMs (days 1-30 post-differentiation) revealed significant baseline differences in beating rate (p<0.01) and contractility amplitude (p<0.01) between iPSC-CMs derived from cardiomyopathic patients and healthy donors. We then subjected iPSC-CM lines to hypoxic conditions (24 hours), to mimic ischaemic injury. Diseased patient-derived lines had significantly decreased viability and metabolic activity when compared to the controls, under normoxic (p<0.01) and hypoxic conditions (p<0.001). Immunoblotting revealed differential expression of cardiac markers and factors implicated in cardiac function, cardioprotection and pathology. Taken together, these results suggest that the detected differences at the cellular level after hypoxia-induced injury might be translatable to the inter-individual variability currently observed in the CVD patient population. The data gathered will prove to be instrumental in future studies of iPSC-CM responses to treatment. With this preliminary study, we hope to shift the focus towards these patient-specific differences at the cellular level, in the search for tailored therapies and a higher standard of care for CVD patients.